2017
DOI: 10.1021/acs.jpcc.6b10838
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Origin of the Stability of Transition-Metal-Doped B14 Drum-Shaped Boron Clusters and Their Assembly into a Nanotube

Abstract: We study the stability of drum-shaped transition metal (TM)-doped boron clusters, M@B n with n = 14 and 16, and M = 3d, 4d, and 5d TM atom using ab initio calculations. Our results show that drum-shaped M@B 14 clusters are favored for M = Cr, Mn, Fe, Co, and Ni, while in other cases, open conical or bowl shaped structures become more favorable. The isoelectronic Ni@B 14 and Co@B 14 − clusters have large highest occupied molecular orbital−lowest unoccupied molecular orbital gaps and these are magic clusters. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…But upon optimization it ends up in an open structure indicating that the formation of a boron cage for this size is unlikely with endohedral doping of an Mo atom. However, recently drum-shaped clusters of 16 boron atoms have been obtained with the doping of a Co atom, while bowl-shaped clusters have been shown [39] to be formed for many of the 3d, 4d, and 5d transition M atoms. Also 14-atom drum-shaped boron clusters have been shown [39] to be favored by doping of some 3d transition M atoms such as Cr, Fe, Co, and Ni.…”
Section: Atomic Structures and Binding Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…But upon optimization it ends up in an open structure indicating that the formation of a boron cage for this size is unlikely with endohedral doping of an Mo atom. However, recently drum-shaped clusters of 16 boron atoms have been obtained with the doping of a Co atom, while bowl-shaped clusters have been shown [39] to be formed for many of the 3d, 4d, and 5d transition M atoms. Also 14-atom drum-shaped boron clusters have been shown [39] to be favored by doping of some 3d transition M atoms such as Cr, Fe, Co, and Ni.…”
Section: Atomic Structures and Binding Energiesmentioning
confidence: 99%
“…[34] The stability of some disk-shaped clusters has been correlated with electronic shell closing at 12 valence electrons. [34] Further, recently bowl-shaped [35,36,37,38,39] and drum-shaped [40,39] structures of boron have been predicted to be stabilized by M atom dopants such as M@B 14 drum with M = Cr, Fe, Co, and Ni, and also with 16 boron atoms such as Co@B − 16 . We have studied M atom encapsulated boron clusters in the size range of 18 to 24 atoms in order to find the smallest cage of free boron clusters besides the drum structures.…”
Section: Introductionmentioning
confidence: 99%
“…However, these two stoichiometries result from different interactions between the orbitals of B 14 and the dopant atom. Xu et al 178,179 analyzed some double-ring B clusters with a TM at the center. They found twelve delocalized orbitals in B 14 Ni, three π-orbitals in the tangential direction filled with six valence electrons following Hückel's (4 n + 2) rule.…”
Section: Introductionmentioning
confidence: 99%
“…However, such works did not include an exhaustive exploration of the PES, so the reliability of this form being the GM is uncertain. 178,179…”
Section: Introductionmentioning
confidence: 99%
“…76,77 For example, Li et al 75 explored the doping of a planar boron cluster B 18 − with a 3d-metal atom Co to gain insight into how dopants can affect the properties of pristine borophenes. Saha et al 78 identified that drum and bowl type clusters become stable on doping transition metals in B 14 clusters. Similarly, Lv and co-workers 68 determined that B 24 upon encapsulation with transition metals transforms into a stable endohedral fullerene structure.…”
Section: Introductionmentioning
confidence: 99%